197 Serial Diffusion Tensor Imaging Demonstrates: White Matter Microstructure in the Preterm Period is not Related to Gestation at Birth. (October 2012) - Huening, BM; Pazderova, L; Ball, G; Tusor, N; Merchant, N; Arichi, T; Allsop, JM; Felderhoff-Müser, U; Rutherford, M; Edwards, AD; Counsell, SJ
Abstract : Background and aims: We have previously shown a dose-dependent effect of prematurity on white matter (wm) microstructure at term equivalent age (TEA). The aim of this study was to determine whether the degree of prematurity at birth is associated with FA values in the early neonatal period. Methods: Inclusion criteria: Preterm birth < 33 weeks gestational age (GA), serial MRI and DTI, first scan ≤ 33 weeks post-menstrual age (PMA), second at TEA. We studied 52 preterm infants, with a median GA at birth of 27+ 1 (24 + 3 – 32 + 6 ) weeks. DTI data were analysed using tract based spatial statistics (TBSS). Voxel based statistics was performed to assess the correlation between GA at birth and FA, corrected for PMA at scan. Results: Scan 1: 31 (25 + 2 – 33) weeks PMA. There were no significant correlations between GA at birth and FA in any WM region. Scan 2: 41 + 1 (38 + 6 – 44 + 1 ) weeks PMA. GA at birth was significantly linearly correlated with FA values in the corpus callosum, internal and external capsule, optic radiation, cerebral peduncles, cingulum and inferior longitudinal fasciculus. Conclusions: These data suggest that diffuse wm injury is not an inevitable consequence of preterm birth, and imply there may be a window of opportunity between birth and term eqivalent age where intervention with appropriate treatments may ameliorate the adverse effects of prematurity on wm development.